2015
DOI: 10.1038/mtna.2015.2
|View full text |Cite
|
Sign up to set email alerts
|

Histone-targeted Polyplexes Avoid Endosomal Escape and Enter the Nucleus During Postmitotic Redistribution of ER Membranes

Abstract: Nonviral gene delivery is a promising therapeutic approach because of its safety and controllability, yet limited gene transfer efficacy is a common issue. Most nonviral strategies rely upon endosomal escape designs; however, endosomal escape is often uncorrelated with improved gene transfer and membranolytic structures are typically cytotoxic. Previously, we showed that histone-targeted polyplexes trafficked to the nucleus through an alternative route involving caveolae and the Golgi and endoplasmic reticulum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 52 publications
9
59
0
Order By: Relevance
“…These results demonstrate a delayed tri colocalization with importin-4 as compared with Rab6, which correlates with the trafficking pattern we identified with our H3-targeted polyplexes and Rab6. 19 We note that in dual colocalization analyses of importin-4 and Sec61 alone, we observed a maximum of 12% colocalization, and in fact, there was less colocalization during mitosis (at the 12 h time point) as compared with the triple colocalization of these two proteins with the H3-targeted polyplexes. The higher coincidence of importin-4 and Sec-61 in the presence of the polyplexes suggested that binding between the H3-targeted polyplexes and importin-4 may drive interactions between importin-4 and Sec61.…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…These results demonstrate a delayed tri colocalization with importin-4 as compared with Rab6, which correlates with the trafficking pattern we identified with our H3-targeted polyplexes and Rab6. 19 We note that in dual colocalization analyses of importin-4 and Sec61 alone, we observed a maximum of 12% colocalization, and in fact, there was less colocalization during mitosis (at the 12 h time point) as compared with the triple colocalization of these two proteins with the H3-targeted polyplexes. The higher coincidence of importin-4 and Sec-61 in the presence of the polyplexes suggested that binding between the H3-targeted polyplexes and importin-4 may drive interactions between importin-4 and Sec61.…”
Section: Resultsmentioning
confidence: 55%
“…19 In these prior studies, we specifically showed that the transport behavior of the H3-targeted polyplexes was conferred in part by interactions with histone H3 effectors, such as H3K4 methyltransferase subunits involved in regulating vesicular transport between late endosomes and the Golgi. 19 These findings motivated the analyses herein to determine whether other H3 effectors, such as the H3 importins, might be involved in shuttling H3-targeted polyplexes into the nucleus during mitosis.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…14 Non-endolysosomal trafficking that does not require endosomal escape, but enables nuclear entry through the endoplasmic reticulum, has been shown to occur for certain nanoparticulates, such as specific histone-targeted nanoparticles, but it has not been demonstrated for the majority of nanoparticle formulations. 15,16 The presence of intracellularly delivered nucleic acid at an acidic pH indicates that the nucleic acid is not in the cytoplasm and is not in the environment required for successful gene expression. Failure to escape the endosome to the cytoplasm can result in nucleic acid degradation when the early endosome transitions to a late endosome/lysosome, typically within an hour following uptake.…”
Section: Introductionmentioning
confidence: 99%